2010
DOI: 10.3109/17549500903469980
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic and phonological errors in children with high functioning autism and Asperger syndrome

Abstract: This study involved a qualitative analysis of speech errors in children with autism spectrum disorders (ASDs). Participants were 69 children aged 5-13 years; 30 had high functioning autism and 39 had Asperger syndrome. On a standardised test of articulation, the minority (12%) of participants presented with standard scores below the normal range, indicating a speech delay/ disorder. Although all the other children had standard scores within the normal range, a sizeable proportion (33% of those with normal stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 20 publications
1
49
1
10
Order By: Relevance
“…5,6,8 Others take an opposite stance. Asperger syndrome and autism present with distinct verbal styles, [18][19][20] motor signs, 21 emotion perception 22 and pragmatic reasoning. 23 There are critical differences in processing strategies adopted by individuals with Asperger syndrome and those with autism.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,8 Others take an opposite stance. Asperger syndrome and autism present with distinct verbal styles, [18][19][20] motor signs, 21 emotion perception 22 and pragmatic reasoning. 23 There are critical differences in processing strategies adopted by individuals with Asperger syndrome and those with autism.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in a longitudinal study of seven years, Anderson et al (2007) found that at the age of 9 years 29.7% of the children who participated in the study never developed speech. In two other studies (Cleland, Gibbon, Peppé, O'Hare, & Rutherford, 2010;Rapin et al, 2009) 33% of 3 to 9 years old children presented with delayed speech, phonological difficulties and speech disorders that remained even after therapy. Furthermore the percentage of children with ASD who present with feeding disorders reaches 46% to 89% (Ledford & Gast, 2006;Kodak & Piazza, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, for these toddlers it may be reflected in more subtle aspects of speech production that were not examined here, such as use of intonation or percent consonants correct in words. Older verbal children with ASD have been shown to produce unusual intonational contours in speech and a higher rate of residual speech errors (Cleland et al, 2010;Shriberg et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers (e.g., Kjelgaard & Tager-Flusberg, 2001) have found that speech ability in older children with ASD is in the average range, even when language and cognitive ability are not. Other researchers (Cleland, Gibbon, Peppé, O'Hare, & Rutherford, 2010;Rapin, Dunn, Allen, Stevens, & Fein, 2009;Shriberg et al, 2011) have identified subgroups of children with ASD with impaired speech production. These differing results highlight the heterogeneity of speech production ability in children with ASD.…”
mentioning
confidence: 99%